Effect of Mn and Cu on the Adsorption of Lead in Soil Sample from South of Shiraz, Iran - Mahzari, M.; Siroienejad, A.; Moalem, M. (Asian Journal of Chemistry, 2012)
Reactions of heavy metals with soils are important in determining the bioavailability and ultimate fate of these metals in the environment. To assess the competitive sorption and sequence of adsorption, we use single- and multi-solute systems consist of Pb, Cu and Mn in surface samples of calcareous soils from southern Shiraz. Heavy metals were added to soils at the rate of 300, 350, 450, 500, 600 and 750 mg kg-1 of Pb and 10 mg kg-1 of Cu and Mn. The samples were incubated for 2 h at room temperature and in pH = 8. Sorption isotherms were characterized using Linear, Freundlich and Langmuir equations. Comparison of R2 indicated most sorption isotherms were well described by Freundlich equation. On the basis of the Kd value, the sequence of the metal adsorption is Pb > Pb - Mn > Pb - Cu, which is related to the first hydrolysis equilibrium constant.